RELEVANSI KONSEP PENDIDIKAN ISLAM IBNU KHALDUN DENGAN PENDIDIKAN MODERN - Rohmah, Siti (Forum Tarbiyah, 2012)
Ibn Khaldun was one of the leaders of Islamic education. His ideas of education were contained in his book of al-Muqaddimah. Ibn Khaldun's thought embodied in the concepts of education is still up to date until today. These concepts include: human resources, the formulation of educational objectives, educational objectives of the idealist to realist, the education aspect of the whole person: perfect man, akhlakul karimah. Ibn Khaldun, as modern education warned educators not to use violence against their students in the  educational process. It is expected that in the learning process there should be interactive relationship between educators and students to achieve educational goals.